2001
DOI: 10.1111/j.1939-1676.2001.tb02307.x
|View full text |Cite
|
Sign up to set email alerts
|

Application of Sartwell's Model (Lognormal Distribution of Incubation Periods) to Age at Onset and Age at Death of Foals with Rhodococcus equi Pneumonia as Evidence of Perinatal Infection

Abstract: The distributions of the incubation periods for infectious and neoplastic diseases originating from point-source exposures, and for genetic diseases, follow a lognormal distribution (Sartwell's model). Conversely, incubation periods in propagated outbreaks and diseases with strong environmental components do not follow a lognormal distribution. In this study Sartwell's model was applied to the age at onset and age at death of foals with Rhodococcus equi pneumonia. The age at onset of clinical signs and age at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1
1

Relationship

5
3

Authors

Journals

citations
Cited by 28 publications
(7 citation statements)
references
References 17 publications
1
6
0
Order By: Relevance
“…Although CTB is an adjuvant known to induce IgA responses at mucosal surfaces [59], we nonetheless observed a significantly higher proportion of foals from the EBRE2 group with increased R. equi -specific nasal IgA compared to the saline control group. We observed that both total and R. equi -specific nasal IgA amounts increased significantly with age, consistent with what has been reported previously for total IgA [49]; to our knowledge, this is the first such report for R. equi -specific nasal IgA. These findings indicate nasal mucosal immunity against R. equi may be relatively diminished in newborn foals, possibly rendering them more susceptible infection.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Although CTB is an adjuvant known to induce IgA responses at mucosal surfaces [59], we nonetheless observed a significantly higher proportion of foals from the EBRE2 group with increased R. equi -specific nasal IgA compared to the saline control group. We observed that both total and R. equi -specific nasal IgA amounts increased significantly with age, consistent with what has been reported previously for total IgA [49]; to our knowledge, this is the first such report for R. equi -specific nasal IgA. These findings indicate nasal mucosal immunity against R. equi may be relatively diminished in newborn foals, possibly rendering them more susceptible infection.…”
Section: Discussionsupporting
confidence: 92%
“…We chose to evaluate immune responses during the first month of life on the basis of evidence that natural infection with R. equi generally occurs early in life [48], [49]. We elected to use ratios (day 32 values relative to day 2) because of considerable variation in absolute values among individual foals and between ages (e.g., declining total antibody concentrations or increasing IFN-γ production with age).…”
Section: Discussionmentioning
confidence: 99%
“…The lack of an effective vaccine is likely attributable to the complexity of immunity to R. equi [7][9], and the finding that foals appear to be infected very early in life [10], [11], when immune responses are naïve or deficient. It is generally accepted that a vaccine must be able to provide foals with protection against infection with R. equi during early life [5].…”
Section: Introductionmentioning
confidence: 99%
“…The relatively reduced/repressed expression of such genes could also reflect immune-modulation of host responses by the pathogen for its survival. If foals generally become infected early in life, as supported by some research findings [7], [8], the genes and associated pathways identified by this study could be targeted for disease prevention or for developing novel therapeutic interventions. For example, enhanced MHC II/Th1-type immune responses might help protect foals against R. equi and other intracellular pathogens (e.g., Salmonella ) during early life.…”
Section: Discussionmentioning
confidence: 53%
“…The finding that R. equi pneumonia is essentially restricted to foals is likely related to exposure and infection during early life and naïve or diminished immune responses of neonatal foals. Although the age at which foals develop R. equi pneumonia remains unknown, epidemiological and clinical evidence indicate that foals are likely infected very early in life [7], [8]. This evidence is consistent with the insidious development of clinical signs in most affected foals [5], and the time required for development of large, pyogranulomatous lesions caused by R. equi .…”
Section: Introductionmentioning
confidence: 55%